THE PLACE OF CONTROLLING IN ENSURING THE COMPETITIVENESS OF THE ENTERPRISE - UZHVA, Alla; IVANCHENKOVA, Larysa; ORIEKHOVA, Alvina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The functioning of any management system at the enterprise is economically justified and aimed at increasing competitiveness. The need for system integration of various aspects of business process management at the enterprise causes the emergence and implementation of the concept of controlling. The controlling service measures ensure the enterprise's efficient operation under the influence of external environmental factors. Prerequisites for the development of controlling are the complication of the external environment of the functioning of enterprises, the need to create adaptation mechanisms to changes in its components, increased competition, and limited opportunities for extensive growth, which lead to the need to optimize internal business processes and optimize costs. This research provides practical insights into the implementation of controlling, offering strategies for enterprises to enhance their competitiveness.The purpose of the article is to study the significance of the implementation of controlling at the enterprise to ensure its competitive activity.The methods of comparison, analysis, and theoretical and logical generalization were applied in the research process. The dialectical research method became the methodological basis.In the process of research, it was proved that the main components of the controlling concept are orientation to the efficient operation of the enterprise in the long term, formation of an organizational structure focused on achieving strategic and tactical goals, creation of an information system adequate to the tasks of target management; division of controlling tasks into cycles, which ensures the iterative nature of planning, execution control, and making corrective decisions. It is proposed to use modern information technologies that allow optimizing the process of enterprise development; the scheme of the place of controlling in the enterprise management system is substantiated; a scientific approach to the establishment and further functionality of controlling is characterized, within which a specific sequence of actions is given, which provides for the organization of the general information environment, planning based on it, ensuring proper accounting of the results of internal activities, control over planned data and accounting data, and ends with the development of necessary measures with regulation of the enterprise's activity process.
Keywords: anti-crisis management; controlling; management accounting; competitiveness; management decisions